(untitled) (Ameghiniana, 2024)
The most common macrofossils in the highly diverse flora from Laguna del Hunco (early Eocene of Chubut, Argentina) are “Celtis” ameghinoi leaves, whose true affinities have remained enigmatic for a century. The species accounts for 14% of all plant fossils in unbiased field counts and bears diverse insect-feeding damage, suggesting high biomass and paleoecological importance. The leaves have well-preserved architecture but lack cuticles or reproductive attachments. We find that the fossils only superficially resemble Celtis and comparable taxa in Cannabaceae, Ulmaceae, Rhamnaceae, Malvaceae, and many other families. However, the distinctive foliar morphology conforms in detail to Dobinea (Anacardiaceae), a genus with two species of shrubs and large herbs ranging from India’s Far East and Tibet to Myanmar and central China, and we propose Dobineaites ameghinoi (E.W. berry) gen et. comb. nov. for the fossils. This discovery strengthens the extensive biogeographic links between Eocene Patagonia and mainland Asia, provides the first fossil record related to Dobinea, and represents a rare Gondwanan macrofossil occurrence of Anacardiaceae, which was widespread and diversified in the Northern Hemisphere at the time. The diverse leaf architecture of Anacardiaceae includes several patterns usually associated with other taxa, and many other leaf fossils in this family may remain misidentified.